The characterization of TBEV of European subtype circulating in Siberia, Russia - I. V. Kozlova; T. V. Demina; S. E. Tkachev; Yu. S. Savinova; E. K. Doroshchenko; O. V. Lisak; Yu. P. Dzhioev; O. V. Suntsova; M. M. Verkhozina; A. I. Paramonov; N. V. Tikunova; V. I. Zlobin; et al. (Эпидемиология и вакцинопрофилактика, 2016)
The aim of the study was to obtain the complex characteristics of tick-borne encephalitis virus (TBEV) of European subtype circulating in Western and Eastern Siberia. Using full-genome sequencing approach it was demonstrated that TBEV strains of European subtype isolated in Siberia are genetically similar to the strains from European part of its habitat range, and with the representatives from South Korea. It was confirmed that the homology of TBEV strains of European subtype isolated in different parts of the virus habitat area from Scandinavian countries in the west to the eastern borders of the area (South Korea) is much higher than the homology level of TBEV strains of Far Eastern and Siberian subtypes. The Siberian population of TBEV of European subtype is presented with two groups of strains called as Eastern Siberian and Western Siberian variants, which differ in the combinations of amino acid substitutions in all proteins except NS2B protein. It is found that TBEV strains of European subtype from Siberia possess high neurovirulence, but some of them, like strains from Europe, demonstrate low invasiveness. It is shown that TBEV strains of European subtype have good adaptive capacity, and therefore, can easily adapt to the circulation in various biocenoses in the territory of different landscape-geographical zones. It was found that the circulation of TBEV of European subtype is fixed in Siberia territory for over 40 years. It was emphasized that in spite of circulation of TBEV of European subtype in the significantly different areas by climatic conditions, topography, landscape, habitat characteristics it possesses a high degree of genome stability.